PENGARUH PEMBERIAN TERAPI PIJAT KAKI TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI BARU DI WILAYAH KERJA PUSKESMAS KURANJI TAHUN 2022 - Jufrika Gusni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Hypertension is a disorder of the blood vessels that results in the supply of oxygen and nutrients carried by the blood being blocked to the body's tissues. Padang City in 2020 the percentage of new hypertension sufferers in the Kuranji Health Center Working Area is 31.33%. The purpose of this study was to determine the effect of providing foot massage therapy on blood pressure in patients with new hypertension in the Kuranji Health Center Working Area in 2022. The research method used is a quantitative quasi-experimental design with a pretest posttest one only group design approach. This research was conducted in the working area of Kuranji Health Center in April - August 2022. The population in this study was 230 people with hypertension, while the sample was 10 respondents who was conducted in July. Data were analyzed univariately using descriptive statistics in the form of mean and standard deviation of each variable and bivariate analysis using paired simple t-test statistical test. From the results of the study, it was found that the average blood pressure before giving foot massage was 154/93, the average blood pressure after giving foot massage was 124/88 mm Hg. There is an effect before and after giving foot massage therapy on blood pressure in patients with new hypertension with a p-value of 0.000.